Kebijakan Hukum Pidana dalam Perlindungan Hukum Terhadap Korban Pelecehan Seksual Secara Verbal - Halawa, Ramadani Saputra; Effendi, Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Criminal provisions regulated in the Criminal Code Book in chapter XIV are formed by the legislators with the intention to provide protection against immoral acts or ontuchte handelingen and against behavioral behaviors both in the form of words and in the form of deeds acts that offend immorality. This is because it contradicts people's views of propriety in the field of sexual life, where the words have been spoken or where the deed has been carried out, as well as in terms of the habits of the local community in carrying out their sexual lives.This research is a normative juridical study or normative legal research. Normative juridical legal research or normative research is research that discusses the principles of law, legal systematics, the extent of legal synchronization, legal history and legal comparison.From the results of the research that the author did can be concluded, the first law enforcement against verbal sexual harassment is still not going well because there are inhibiting factors in the process. Obstacles - obstacles include: Factors of the law itself, Factors of law enforcement officials, Factors of the community, Second, overcoming crime is done through several stages, namely the formulation stage, the application stage and the execution stage. In the process of criminalization also must pay attention to two central issues in criminal law policy. Protection against victims of verbal abuse by catcalling can be done through the rights enshrined in Article 5 of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, Law Number 39 of 1999 Concerning Human rights.Kanci Words: Criminal Law Policy - Legal Protection - Verbal Sexual Harassment